Chemical Treatments for Reducing the Yellow Discoloration of Channel Catfish (Ictalurus punctatus) Fillets. Issue 10 (11th September 2013) - Li, Yilin; Liu, Shaoyang; Cline, David; Chen, Shengshun; Wang, Yifen; Bell, Leonard N.
Abstract: The effect of chemical pretreatments on the color and carotenoid content of yellow discolored channel catfish fillets was studied. The color and carotenoid content of the fillets were analyzed by the L*a*b* color system and high‐performance liquid chromatography, respectively. Untreated fillets turned more yellow and darker after 12‐d storage. Sodium bicarbonate had a beneficial effect on reducing the degree of yellowness, but the fillets still turned darker after storage. Sodium bisulfite gave the best results with fillets becoming less yellow and brighter after storage. Ascorbic acid, butylated hydroxyanisole, citric acid, and sodium metabisulfite were not successful at reducing the discoloration. The sum of carotenoid contents of untreated fillets decreased significantly ( P < 0.05) during storage as compared to the fresh fillets. However, the sum of the carotenoid contents of fillets treated by various chemicals was not significantly ( P > 0.05) different from the fresh or untreated fillets. The appearance of catfish fillets may be improved during storage by pretreating with sodium bisulfite.